Impacts of Snow Darkening by Deposition of Light‐Absorbing Aerosols on Hydroclimate of Eurasia During Boreal Spring and Summer. Issue 16 (18th August 2018) - Lau, William K. M.; Sang, Jeong; Kim, M. K.; Kim, K. M.; Koster, R. D.; Yasunari, T. J.
Abstract: In this study, we used the NASA GEOS‐5 climate model to investigate the impact of snow darkening by deposition of light‐absorbing aerosols on the hydroclimate of Eurasia during boreal spring and summer. Two sets of 10‐member ensemble model integrations with prescribed sea surface temperature were carried out for 10 simulated years (2002–2011); one includes snow‐darkening effects (SDE) by light‐absorbing aerosols and one does not (NSDE). Differences between the two experiments in the hydroclimates over Eurasia were evaluated. Results show that SDE warming is most pronounced during the melting season due to strong snow‐albedo feedback in the vicinity of the retreating seasonal snowline. SDE spurs a wet‐first‐dry‐later modulation of the surface energy and water balances, characterized by an accelerated (days‐to‐weeks) snowmelt, accompanied by excessive runoff and a warming and wetting of the land (relative to NSDE) during the early melting season. The snowmelt is followed by a fast desiccation of the land during the late melting, and early warming season, and then a prolonged warmer and drier land, through the boreal summer. The prolonged warming is sustained by atmospheric conditions favorable for the development of atmospheric blocking, that is, higher middle‐to‐upper‐tropospheric geopotential height, lower relative humidity, reduced cloudiness, and enhanced atmospheric subsidence. Overall, SDE by light‐absorbing aerosols leads to a warmer and drier boreal summer hydroclimate, increasing the frequency of the top 5 and 1% extreme hot days (as defined by NSDE statistics) over western and northern Eurasia by approximately threefold and tenfold, respectively. Key Points: Snow darkening by light‐absorbing aerosols spurs accelerated snowmelt, runoff, and warming of Eurasian land during boreal spring Land drying persists through summer due to depleted supply of freshwater supply from accelerated snowmelt and increased evaporation Atmosphere‐land interaction exacerbates the hot and dry climate, enhancing the intensity and frequency of summertime extreme heating days